Islam dan Konservasi Lingkungan (Telaah Pemikiran Fikih Lingkungan Yusuf Al-Qaradhawi) - Aziz Gufron (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
The article tries to uncover the vision of Dr. Yusuf al-Qaradhdwi of allegiance from the perspective of Islamic Laiv (Islamic Sharia), and then attach conditions to sell Indonesia, which caused various problems allegiance. We began the analysis given to the basic principles of the teachings auspices of allegiance in the Islamic Sharia. When al-Qaradhawt and allegiance every defense official in this world, but there are aspects of the pledge it had rights in general and Muslims inparticular deviation and most importantly respect the ethics of the sale. Founded ideas al-Qaradhdwt care pledge from the perspective of jurisprudence and mysticism, which evolved from the Holy Koran and the Sunna. In terms of jurisprudence there orders attach revival of agricultural (ihya’ al-mawat), hygiene and others. The mysticism of hand - especially the concept of its an - there attitude of fairness, honesty, thanks, conviction, and ideals. The article also look at the conditions of problems in our country today, such as the problem of the sea, forest and others